Senegal : Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This paper focuses on Senegal's second poverty reduction strategy paper (PRSP-II). It summarizes the results of the participatory PRSP review process prior to final validation and adoption by the government. As an economic and social policy document for growth and poverty reduction that draws legitimacy from an underlying participatory process, it sets poverty reduction targets for the medium and long terms, defines progress indicators, and establishes annual and intermediate targets. It also identifies the resources to be mobilized to achieve the desired results.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet